Detection of Mycobacterium avium subspecies paratuberculosis in several herds of arctic caribou (Rangifer tarandus ssp.) - Forde, Taya; Côté, Steeve D.; Orsel, Karin; Taillon, Joëlle; De Buck, Jeroen; Cuyler, Christine; Davison, Tracy; Elkin, Brett; Kelly, Allicia; Kienzler, Martin; Popko, Richard A.; Veitch, Alasdair; et al. (Journal of Wildlife Diseases, 2020)
Mycobacterium avium subspecies paratuberculosis (MAP) is a common pathogen in domestic ruminants that causes granulomatous inflammation of the small intestine leading to emaciation and wasting. Clinical disease (Johne’s disease) is also reported for several wild ruminant species. Between 2007 and 2009 we collected 561 fecal samples from caribou (Rangifer tarandus ssp.) representing 10 herds of migratory caribou, two herds of caribou from Greenland, and three populations of boreal woodland caribou. Feces were tested for MAP by bacterial culture and PCR targeting the IS900 insertion sequence. In total, 31 samples from eight different populations representing all three ecotypes were found positive for MAP by PCR, with one sample from the Rivière-aux-Feuilles herd also being culture positive for the type II (cattle) strain. The proportion of positive animals was particularly high in the Akia-Maniitsoq herd in Greenland, and Rivière-aux-Feuilles and Rivière-George herds in northeastern Canada (23.4, 11.5, and 10.0%, respectively). Our results indicate that MAP is present in several caribou herds of different ecotypes in northern Canada and Greenland and that MAP circulates within wildlife populations that do not have ongoing contact with domestic livestock. The epidemiology, pathogenicity, and effects on the health of caribou in northern ecosystems remain unknown.